Development of transgenic lines from a male-sterile potato variety, with potential resistance to tecia solanivora povolny (2012)
Male sterility is a very important characteristic for environmental safety in genetically modified (GM) plants, particularly in the release of transgenic plants in the centers of origin or high biodiversity areas. In order to contribute to the development of environmentally safe agricultural technologies that allow the proper use of transgenic potato crops in Colombia, this project developed transgenic potato cry1Ac of Bacillus thuringiensis (Bt), lines that are potentially resistant to T. solanivora, from the male-sterile variety Pastusa Suprema (PS) (Solanum tuberosum ssp. andigena). Modifications were made to the Agrobacterium tumefaciens mediated-transformation protocol which allowed the genetic transformation of leaves of in vitro plants, with transformation efficiencies of 22 and 37%. Cry1Ac protein levels in transgenic leaves ranged from 88 to 639 ng mg-1 of fresh leaf tissue, suggesting a better potential plant resistance. This is the first report on transgenic lines with potential resistance to T. solanivora from a male-sterile variety of S. tuberosum ssp. andigena.